Harnessing Soft Computation for Diabetes Care: A Computational Approach to Metabolic Disorders - Muntadher Hasan Naeemah; Tabarek Amer Hasan; Riyadh Majid Qasim Al Boed; Ali Faris Hamzah; Noor Mohammed Abd Al_Hussain; Baraa Mahdi Salih (Peerian Journals Publishing, 2024)
Diabetes mellitus (DM), commonly known only as diabetes, is a group of metabolic disorders characterized by high blood sugar levels over a prolonged period. Symptoms often include frequent urination, increased thirst and increased appetite. If left untreated, diabetes can cause many health complications. Acute complications can include diabetic ketoacidosis, hyperglycemic hyperosmolar state, or death. Serious long-term complications include cardiovascular disease, stroke, chronic kidney disease, foot ulcers, nerve damage, eye damage and cognitive impairment . Soft computation refers to a set of new computational methods in computer science, artificial intelligence, machine learning, and many other applied fields. In all these fields, the study, modelling and analysis of very complex phenomena is needed, and accurate scientific methods have not been able to solve them easily, analytically and thoroughly in the past. Soft calculations are devoted to human beings compared to the hard calculations and measures taken by their mind in order to resolve problems, while the hard methods arise from nature and the way the machine behaves
Keywords: Diabetes mellitus; Soft computation; Computational approach; Metabolic disorders